Chronic Peripheral Inflammation Causes a Region-Specific Myeloid Response in the Central Nervous System - Süß, Patrick; Hoffmann, Alana; Rothe, Tobias; Ouyang, Zhengyu; Baum, Wolfgang; Staszewski, Ori; Schett, Georg; Prinz, Marco; Krönke, Gerhard; Glass, Christopher K.; Winkler, Jürgen; Schlachetzki, Johannes (Cell Reports, 2020)
Systemic immune dysregulation contributes to the development of neuropsychiatric and neurodegenerative diseases. The precise effect of chronic peripheral immune stimulation on myeloid cells across anatomical brain regions is unclear. Here, we demonstrate brain-region-specific differences in myeloid responses induced by chronic peripheral inflammation. This shift in the myeloid compartment is associated with the appearance of an inflammatory myeloid subpopulation in the cortex, striatum, and thalamus accompanied by regional transcriptomic fingerprints that include induction of chemokines, complement factors, and endothelial adhesion molecules. In contrast, myeloid immune responses within the hippocampus and cerebellum are subtle or absent. Treatment with the anti-tumor necrosis factor α (anti-TNF-α) antibody infliximab ablates the region-specific inflammatory response. A region-specific myeloid cell response to chronic peripheral inflammation is observed in postmortem brains from individuals with rheumatoid arthritis. Our data suggest that chronic peripheral inflammation has heterogeneous effects on the brain, as evidenced by the spectrum of myeloid cell responses observed across brain regions.
CRIS-Team Scopus Importer:2020-03-31
Keywords: blood-brain barrier; brain regions; chronic peripheral inflammation; CNS myeloid cells; human rheumatoid arthritis; microglia